Flow cytometric immunoassay using E. coli with autodisplayed Z-domains - Park, Min; Bong, Ji-Hong; Yoo, Gu; Jose, Joachim; Kang, Min-Jung; Pyun, Jae-Chul (ELSEVIER SCIENCE INC, 2013)
Recently, we reported a highly sensitive immunoassay using Escherichia coli cells with autodisplayed Z-domains. In this work, E. coli cells with autodisplayed Z-domains were applied to the flow-cytometry-based simultaneous detection of multiple analytes. The E. coli cells were doubly transfected to express a fluorescent protein (tdTomato) in the cytosol and the autodisplayed Z-domains on the outer membrane. By using E. coli cells with only the autodisplayed Z-domains, immunoassay of multiple analytes could be performed simultaneously on the same sample. Flow cytometry can be used to identify the immunoassay type by simultaneously detecting the fluorescence signal from the cytosol (tdTomato) and the fluorescence from the outer membrane, enabling the quantification of bound analytes after treatment with additional fluorescently labeled antibodies. To demonstrate the immunoassay of multiple analytes by using flow cytometry, human hepatitis B virus surface antigen (HBsAg) and C-reactive protein (CRP), a broad spectrum inflammation marker, were used as model analytes. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: ESCHERICHIA-COLI; SPR BIOSENSOR; RHEUMATOID-ARTHRITIS; PROTEIN-A; IMMUNOSENSORS; MARKERS; SYSTEM; ASSAY